The Phenomenon of Civil Dispute Claim Settlement through Police Report a Restorative Justice Approach - Stephan Anggita Hutagaol; Abdul Muta'ali; Basir S; Agus Ady Wijaya; Markus Marselinus Soge (Budapest International Research and Critics University, 2022)
This research was initiated by the phenomenon of civil disputes which were reported to the police, so what was originally civil disputes became criminal domain. The principle of restorative justice is a breakthrough in the criminal legal system seeks to provide justice to the parties (especially to the victims) by prioritizing recovery to its original state (before crime happened) and restore good relationship in the society, instead in factual (das sein) restorative justice was used to resolve civil cases such as account receivable claim or bad debt through police reports, which theoretically (das sollen) account receivable claim or bad debt should be resolved through the mechanism of civil law proceedings. The author chooses qualitative research method type of document study (literature study) using primary data and secondary data as sources of data in this study, including examining police regulations and restorative justice books written by police writers, police practitioners who are also academics, to understand the problems and to answer the research questions, as well as to achieve the research objectives. From this research the authors found that there is privilege in using criminal approach that was not found in the civil law proceedings, and by using the principle of restorative justice it is more possible for the parties to reconcile in a criminal case.